Metallothionein Biosynthesis in Human RBC Precursors - Rahman, Mohammad Tariqur; Vandingenen, Anick; De Ley, Marc (S. Karger AG, 2000)
The in vitro biosynthesis of metallothionein (MT) has been investigated in RBC precursors from human cord blood in order to support the hypothesis for the nucleated precursor origin of MT in human red blood cells (RBC). Human RBC precursors are obtained by (i) separating glycophorin A+ (gly A+) cells using a magnetic cell sorting (MACS) technique and by (ii) ex vivo expansion of precursors BFU-E (burst forming unit-erythroid) on methylcellulose semi-solid culture media from mononuclear cells of cord blood. Biosynthesis of MT is detected at the protein level, by immuno-histochemical staining using a mouse monoclonal antibody (E9) in ex vivo expanded RBC precursors obtained from BFU-E. Expression of MT is also detected at the mRNA level by MT specific reverse transcriptase polymerase chain reaction (RT-PCR) both in ex vivo expanded precursors from BFU-E and in MACS separated gly A+ cells. In addition, the expression of the fetal form of MT, MT-0 (also known as MT-1H) at the mRNA level in glycophorin A+ cells, is also confirmed by cDNA sequencing. With these observations, to our knowledge, MT biosynthesis in human erythroid precursors is reported for the first time. Moreover, the current findings of MT-0 expression at the mRNA level in gly A+ RBC precursors of hCB has added one more member in the list of cells/organs like fetal liver, human monocytes, non-neoplastic tissues of adenocarcinoma etc., in which the expression of the human fetal form of MT, i.e. MT-0, has also been reported.